Dolgoročno zagotavljanje avtentičnosti in vzdrževanje celovitosti elektronsko hranjenega gradiva - Halas, Helena (Knjižnica, 2011)
Long term preservation of electronic data requires introduction of specific technology solutions and organizational measures in order to provide stable environment for electronic record preservation. System solutions must support basic principles of electronic preservation: accessibility of data, usability or reproduction of data in usable form and integrity/authenticity provision including time existence for preserved content. Due to their nature, electronic data may become subjects of manipulation without recursive traceability of content alteration. In order to preserve usability of preserved data, electronic preservation system must provide appropriate measures for demonstrating unalterability of data for the entire preservation period. In this paper technology approach for demonstrating integrity and authenticity of archived data on long term basis is presented. Presented technological concept deals with any type of documentation or archiving material and provides creation of additional security assertions or evidence records that are needed to demonstrate the authenticity and integrity of the material anytime during the archival period. The evidence record syntax (ERS), which has been standardized by international organization body for internet standards (IETF), presents universal techniqueof security assertions generation and their maintenance for integrity preservation based on document hashing, hash treeing and integration of (qualified) time stamps of trusted third parties. Using re-time-stamping methods created security assertions may endure their validity for longest periods of time until retention periods of archived data expires. In the paper complementary organizational rules for technology solutions are presented as well, providing an all around overview of long term preservation of data in authentic, reliable and secure manner.
Keywords: elektronski podatki; dolgoročna hramba; avtentičnost; celovitost; varnostne vsebine; evidenčni podatki; digitalni podpis